Molecular gas across cosmic time. Issue Volume 15:Issue S352(2019) (June 2019) - Magdis, Georgios E.
Abstract: We have entered an era where the gas mass estimates of distant galaxies do not rely on a single tracer but rather on an inventory of different and independent methods, much like the case for the determination of the star formation rate (SFR) of the galaxies. This is crucial as the traditional M gas tracers, i.e. low-J CO transition lines and dust continuum emission are becoming highly uncertain as we move to higher redshifts due to metallicity and CMB effects. Here, we present a homogeneous and statistically significant investigation of the use of atomic carbon as an alternative M gas tracer (Valentino et al. 2018 ) and provide evidence of optically thick far-IR emission in high− z starbursts that point towards higher dust temperatures and lower dust and gas mass estimates than previously inferred (Cortzen et al. 2019, submitted). Finally, we present direct observations of the effect of the CMB on the far-IR SEDs of high-z SBs, manifested by unphyscally large (β = 2.5–3.5) apparent spectral indexes in R-J tail (Jin et al. 2019, submitted).